Composition of TWIST1 dimers regulates fibroblast activation and tissue fibrosis. Issue 1 (25th April 2016) - Palumbo-Zerr, Katrin; Soare, Alina; Zerr, Pawel; Liebl, Andrea; Mancuso, Rossella; Tomcik, Michal; Sumova, Barbora; Dees, Clara; Chen, Chih-Wei; Wohlfahrt, Thomas; Mallano, Tatjana; Distler, Alfiya; et al.
Abstract : Objectives: TWIST1 is a member of the class B of basic helix-loop-helix transcription factors that regulates cell lineage determination and differentiation and has been implicated in epithelial-to-mesenchymal transition. Here, we aimed to investigate the role of TWIST1 for the activation of resident fibroblasts in systemic sclerosis (SSc). Methods: The expression of Twist1 in fibroblasts was modulated by forced overexpression or siRNA-mediated knockdown. Interaction of Twist1, E12 and inhibitor Of differentiation (Id) was analysed by co-immunoprecipitation. The role of Twist1 in vivo was evaluated using inducible, conditional knockout mice with either ubiquitous or fibroblast-specific depletion of Twist1. Mice were either challenged with bleomycin or overexpressing a constitutively active transforming growth factor (TGF)β receptor I. Result: The expression of TWIST1 was increased in fibroblasts in fibrotic human and murine skin in a TGFβ/SMAD3-dependent manner. TWIST1 in turn enhanced TGFβ-induced fibroblast activation in a p38-dependent manner. The stimulatory effects of TWIST1 on resident fibroblasts were mediated by TWIST1 homodimers. TGFβ promotes the formation of TWIST1 homodimers by upregulation of TWIST1 and by induction of inhibitor of DNA-binding proteins, which have high affinity for E12/E47 and compete against TWIST1 for E12/E47 binding. Mice with selective depletion of Twist1 in fibroblasts are protected from experimental skin fibrosis in different murine models to a comparable degree as mice with ubiquitous depletion of Twist1 . Conclusions: Our data identify TWIST1 as a central pro-fibrotic factor in SSc, which facilitates fibroblast activation by amplifying TGFβ signalling. Targeting of TWIST1 may thus be a novel approach to normalise aberrant TGFβ signalling in SSc.